Factors Influencing The School Literacy Movement in Embedding Students’ Reading Interest at Elementary School of South Sumatera - Amir Hamzah; Anisa Astrid; Dian Andesta Bujuri; Nurlaeli Nurlaeli; Elvira Destiansari (JIP Jurnal Ilmiah PGMI, 2023)
This research aims to determine the supporting factors and inhibiting factors for School Literacy Movement program activities in fostering students' interest in reading in South Sumatra. The research method used is a qualitative method using a phenomenological design approach which is used on multiple sites in three schools, namely IBA Elementary School of Palembang, 1 State Elementary School of Indralaya and 3 Elementary School of Kayuagung. The results of this research show that the supporting factors in the School Literacy Movement program at three schools in fostering students' interest in reading in class IV are: A complete library; Cozy Reading Corner; Interesting wall material; Attractive Reading Park and School Literacy Cart; Clear Identity Board; Literacy Tree; beautiful school gardens; Involvement of parents and the public; creative School Literacy Movement Team; School Garden; Training and Study Tour ; and an attractive Reading Campaign Poster. Factors that become obstacles in implementing the School Literacy Movement program in the three schools in fostering students' interest in reading in class IV. Students are lazy about studying; Students are not used to reading; Library management is not yet supported by officers who have librarian qualifications and parent collaboration is not good. Based on this, it can be concluded that fostering interest in reading in elementary school students in South Sumatra is influenced by both supporting and inhibiting factors.